The elusive final set - are tennis finals always close run contests? - Fanshawe, T. (Significance, 2013)
At the 2013 Wimbledon Championships, the top two seeded players reached the final of the men`s singles competition, while two relative outsiders reached the final of the women`s. Many commentators predicted close, exciting finals and appeared surprised when both matches were decided in straight sets. Is this as unlikely as it first appeared? To answer this I examined the results from all Wimbledon singles finals to see what the statistics tell us.